A Theory of Why the Ruthless Revolt. (6th July 2016) - Hendrickson, Joshua R.; Salter, Alexander William
Abstract : We examine whether ruthless members of society are more likely to revolt against an existing government. The decision of whether to participate can be analyzed in the same way as the decision to exercise an option. We consider this decision when there are two groups in society: the ruthless and average citizens. We assume that the ruthless differ from the average citizens because they invest in fighting technology and therefore face a lower cost of participation. The participation decision then captures two important (and conflicting) incentives. The first is that, since participation is costly, there is value in waiting to participate. The second is that there is value in being the first mover and capturing a greater share of the "spoils of war" if the revolution is successful. Our model generates the following implications. First, since participation is costly, there is some positive threshold for the net benefit that must be met before any individual decides to participate. Second, if the ruthless do not have a significant cost advantage, then one cannot predict, a priori, that the ruthless lead the revolt. Third, when the ruthless have a significant cost advantage, they have a lower threshold and always enter the conflict first. Finally, existing regimes can delay revolution among one or both groups by increasing the cost of participation.